Growing Prevalence and Incidence of Diabetes in Republic of Macedonia in past 5 years based on data from the national system for electronic health records - Ahmeti, Irfan; Bitoska, Iskra; Markovikj, Snezhana; Shukarova Angelovska, Elena; Jovanovska Mishevska, Sasha; Kochinski, Goran (Scientific foundation Spiroski, 2020)
Introduction. Diabetes is a chronic metabolic disease characterized with a rapid progression of prevalence in last 3 decades, especially in countries with low and middle income. Next three decades this number of diabetes in the world is expected to be doubled. Early diagnosis and appropriate management of diabetes is the primary way to prevent and delay cardiovascular complications. Patients and methods. In this retrospective study, we used the data from National electronic system e-health which was performed in late 2014, wich gives us nearly precise data, and we made statistical analysis for diabetes in last 5 years (2015-2019). Results. In 2015 we have registered 103480 patients with DM, in 2016 108130 patients, in 2017 114408, in 2018 119999 and in 2019 124450 patients with DM. 95% of patients are with T2DM and 4, 1% with T1DM. According the data from State statistical office for population of Republic of Macedonia, the prevalence of T2DM for the years 2015-2019 is as follows: 5,66% in 2015, 6.13% In 2016, 6.55% I 2017, 7,06% in 2018 and 7,2% in 2019. Conclusions. The number of registered patients with diabetes in last 5 years has grown up for 20970 or 20%, in the last 5 years the number of patients with type 2 diabetes has grown up for 18272 patients or 11%. The prevalence of T2DM has increased for 1.54%. Involvement of primary health care professionals has improved the early diagnosis of type 2 diabetes.